The politics of independence: Police Accountability - Zuckerberg, Joaquín (Frónesis, 1970)
This paper analyses the principle of police independence which came into being with the establishment of liberal democracies such as Canada. Nowadays, there are increasing signs that the traditional view of police independence held in a liberal democracy has become obsolete. In Canada, the Executive's use of police forces as a political instrument has resulted in an increasing demand for accountability of police actions. These calls for change have been repeatedly rejected on the basis of a potential danger posed to the independence of the police. This produces an impasse in which the legitimacy of police actions is increasingly challenged. The relation between police independence and accountability in liberal democracies, therefore, reveals itself as highly conflictive and invites a reformulation of the principle of police independence.